2014
DOI: 10.1007/s11060-014-1686-9
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine potentiates temozolomide cytotoxicity by inhibiting mitochondrial autophagy in glioma cells

Abstract: Mitochondrial autophagy eliminates damaged mitochondria and decreases reactive oxygen species (ROS). The autophagy inhibitor chloroquine (CQ) potentiates temozolomide (TMZ) cytotoxicity in glioma cells, but it is not known whether CQ does this by inhibiting mitochondrial autophagy. The effects of CQ and TMZ on MitoSOX Red fluorescence, a mitochondrial ROS indicator, and cell death were examined in rat C6 glioma cells. Mitochondrial autophagy was monitored by the colocalization of MitoTracker Red fluorescence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 30 publications
2
51
1
Order By: Relevance
“…However, in the CQ-pretreated cells, the LC3II expression was markedly increased compared to that following TDCIPP treatment alone. CQ prevents endosomal acidification, thereby inhibiting lysosomal enzymes and causing the accumulation of LC3II (Hori et al, 2015). Thus, 3-MA and CQ can inhibit autophagy and increase apoptotic cell death in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, in the CQ-pretreated cells, the LC3II expression was markedly increased compared to that following TDCIPP treatment alone. CQ prevents endosomal acidification, thereby inhibiting lysosomal enzymes and causing the accumulation of LC3II (Hori et al, 2015). Thus, 3-MA and CQ can inhibit autophagy and increase apoptotic cell death in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 98%
“…The SH-SY5Y cells were treated in the presence of the autophagy inhibitor CQ. CQ is a lysosomotropic agent that prevents endosomal acidification, thereby inhibiting lysosomal enzymes and causing the accumulation of LC3II (Hori et al, 2015). CQ (10 mM) increased LC3II accumulation (Fig.…”
Section: Tdcipp Induced Autophagy In Sh-sy5y Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be cytoprotective, helping the cell to survive or it can be cytotoxic, leading to cell death [1516]. Autophagy has been shown in various tumor cell systems, including hepatocellular carcinoma and glioblastoma to protect cells against the cytotoxic effect of radiation or chemotherapy [4244]. In nasopharyngeal carcinoma, several studies have demonstrated the induction of autophagy by radiation mostly using one cell line [3132, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the existing studies addressing the effects of CHQ in glioma cells have used conventional serum-dependent cell lines that lack stemness properties and/or poorly recapitulate characteristic features of human GBs. For example, the human glioma cell line U87MG, which has been widely used as an experimental model for investigating biological responses mediated by CHQ (21, 22, 29, 30, 81, 82) does not reproduce certain characteristic traits of GBs such as an invasive tumor phenotype, intra-tumoral heterogeneity and high degree of intrinsic radio-resistance. Considering that GSCs are fundamentally distinct from non-stem glioma cells, it is conceivable that their responses to CHQ might also differ from those operating in the latter ones.…”
Section: Chloroquine As Potential Anti-cancer Drug: Unsolved Questionmentioning
confidence: 99%